Upaya Masyarakat dalam Memanfaatkan Pondok Pesantren Darul Ulum Untuk Meningkatkan Ekonomi di Dusun Rejoso Desa Ngumpul Kecamatan Jogoroto Kabupaten Jombang - Muhammad Za’im Mutahajjidir Rohim; Bagus Setiawan (STIKes Ibnu Sina Ajibarang, 2024)
This research is motivated by the existence of the Darul Ulum Islamic Boarding School which is located in Rejoso Hamlet where the people in the hamlet are dominant in their livelihoods as private employees, not a few people from young people who prefer to migrate rather than explore the potential that exists in the region, because the problem is that not all local people can take advantage of the economy with the existence of the Islamic boarding school. The focus of research in writing this thesis is. 1. How are the efforts of the community in utilizing the Darul Ulum Islamic Boarding School to improve the community's economy in Rejoso Hamlet, Ngumpul Village, Jogoroto District, Jombang Regency? 2. How is the impact of the Darul Ulum Islamic Boarding School on the economic increase in Rejoso Hamlet, Ngumpul Village, Jogoroto District, Jombang Regency? To find out the community's efforts in utilizing the Darul Ulum Islamic Boarding School to improve the community's economy in Rejoso Hamlet, Ngumpul Village, Jogoroto District, Jombang Regency. 2. To find out the impact of the Darul Ulum Islamic Boarding School on economic improvement in Rejoso Hamlet, Ngumpul Village, Jogoroto District, Jombang Regency. The method used in this research is descriptive qualitative approach. The research location is in Rejoso Hamlet, Ngumpul Village, Jogoroto District, Jombang Regency. Data sources taken using primary and secondary data. Data collection by observation, interview, and documentation. Data analysis in the form of data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data. From the results of the data discussion it can be seen that. Community efforts in utilizing Darul Ulum Islamic Boarding School to improve the community's economy are opening a laundry service business, food business, and grocery store. 2. The positive impact of the existence of the Darul Ulum Islamic boarding school increases income, opens up jobs, facilitates access to daily needs. While the negative impact is the high number of business competitors, price differences and payment systems, cheating between business owners.